The Influence of Service Quality, Price, and Brand on Customer Satisfaction in Hijab Fashion: An Islamic Law Perspective - Maharani, Syifa; Mansah, Adi (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2025)
This study examines how service quality, price, and brand shape customer satisfaction in the hijab fashion market and interprets the findings through an Islamic law lens (maqāṣid al-sharīʿah). Using a mixed-methods design, we surveyed hijab consumers who had purchased at least twice in the last six months (n = 120; purposive sampling) and complemented the statistics with brief interviews/document reviews. Instruments passed validity–reliability checks and classical assumptions (normality, multicollinearity, heteroskedasticity). Multiple linear regression shows that service quality, price, and brand each have a positive, significant effect; jointly they are significant (F = 13.957, p < 0.001) with R² = 0.265 (Adjusted R² = 0.246), indicating moderate explanatory power. Interpreted normatively, service quality aligns with iḥsān–samḥah (courteous, facilitative service), fair and transparent pricing reflects ‘adl, and trustworthy branding embodies ṣidq–amānah; satisfaction is framed as tarāḍin, supported by khiyār (clear return/exchange). These values cohere with the maqāṣid emphasis on protecting wealth (ḥifẓ al-māl) and avoiding harm while realizing benefit (dar’ al-mafāsid wa jalb al-maṣāliḥ). Managerially, firms should strengthen after-sales service, price transparency, and honest brand communication, and operationalize Sharīʿah-compliant policies (e.g., clear product information and accessible returns) to foster sustainable satisfaction and loyalty.Keywords: service quality; price; brand; customer satisfaction; Islamic law; maqāṣid al-sharīʿah